2015
DOI: 10.1080/13540602.2014.995475
|View full text |Cite
|
Sign up to set email alerts
|

Early education teachers’ conceptualizations and strategies for managing closeness with the class in child care

Abstract: This study investigated teachers' experiences of closeness during interactions with the group of children in child care. Structured interviews were conducted with 24 female teachers who were teaching children between the ages of three and five (mean age = 3.9) regarding their perceptions of closeness with the group of children in the class. Qualitative analyses of the interviews revealed a group solidarity domain of teacher-group relationships composed of three dimensions which comprise emotional solidarity, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Childcare workers who report less control in their roles acknowledge lower closeness in their relationships with children (Whitaker et al., ). Qualitative research also has revealed a construct that approximates the group‐level closeness variable identified in quantitative studies (Quan‐McGimpsey, Marziliano, Hassen, Brown, & Kuczynski, ). In this sample, αs were .73 and .70 for closeness and conflict, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…Childcare workers who report less control in their roles acknowledge lower closeness in their relationships with children (Whitaker et al., ). Qualitative research also has revealed a construct that approximates the group‐level closeness variable identified in quantitative studies (Quan‐McGimpsey, Marziliano, Hassen, Brown, & Kuczynski, ). In this sample, αs were .73 and .70 for closeness and conflict, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…In the same way as organizational culture and social arena influence emotional distance/closeness among employees, principals, teachers and students may feel emotional distance/closeness interchangeably. Thus, research showed that emotional closeness includes solidarity, mutuality and intimacy (Quan-McGimpsey et al, 2015). According to O'Connor (2008), emotional closeness is an integral aspect of teaching and, therefore, becomes a part of the teacher's professional identity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In the same way as organizational culture and social arena influence emotional distance/closeness among employees, principals, teachers and students may feel emotional distance/closeness interchangeably. Thus, research showed that emotional closeness includes solidarity, mutuality and intimacy (Quan-McGimpsey et al. , 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thomas Torbjornsson and Lena Molin [15], about exploring solidarity attitudes among high school students in Sweden in 2015, involved twenty-two third-year students. The results of the research show that students do not recognize solidarity because the concept and case history of solidarity have never been raised in the class.…”
Section: A Relevant Studiesmentioning
confidence: 99%